Shadow Self and Its Ethical Sense in Superman Robots - Bethari, Chili Podhang; Pasopati, Rommel Utungga (Proceeding International Conference on Religion, Science and Education, 2024)
This article explains correlations of Superman Robots of DC Comic character and ethical understandings of AI. Through qualitative approach and explorative method, this paper answers question of ‘how may shadow self be represented on ethical values of Superman Robots?’. In analysis, Superman Robots are dummies, made by Superman, used to deal with everyday business of Superman. Those work as shadow self-indicated in personality archetype by Carl Jung. Those are not real self of Superman but work like he is existent throughout the world. This is in line with current development of AI that tends to shape anonymity that may question the ethical aspect of self. While real self could be blamed for any matter, shadow self is otherwise since its authenticity is blurred. In conclusion, Superman Robots reflect shadow self in which its ethical sense will always return to its real person. It is similar to anonymity in AI that require real person to be ethically responsible.